Test automation engineering handbook - Sambamurthy, Manikandan (Packt Publishing, 2023)
Understand test automation and implement it in Web, Mobile, and APIs effectively About This Audiobook Learn how to automate your tests with the help of practical examples Understand how to bridge the gap between testing and test automation Explore test automation strategies for different platforms In Detail This audiobook helps you build a better understanding of test automation and aids in bridging the gap between testing and test automation. The audiobook has been divided into three sections with the first section focusing on preparing you for testing and test automation fundamentals. By the end of this section, you'll have an understanding of some common automation terms, definitions, and roles. The second section covers the practical implementation of test automation for mobile, web, API and performance. The third section will help you understand how test automation works with CI/CD, and explore the common issues and pitfalls when executing test automation. By the end of this audiobook, you'll have a better understanding of automation, addressing the common pain points and best practices around test automation. Audience This audiobook is for manual testers who want to enter the field of test automation and developers who want to learn more about test automation.